A Combined Homotopy‐Optimization Approach to Parameter Identification for Dynamical Systems. Issue 1 (18th November 2019) - Schäfer, Kai; Flaßkamp, Kathrin; Fliege, Jörg; Büskens, Christof
Abstract: When applying the single shooting approach to solve nonlinear dynamic parameter identification problems, difficulties like undesired minima can occur. To circumvent this, we apply a homotopy continuation to find global minima. In contrast to the literature, we reduce the resulting series of optimization problems to a single one which leads us to the opportunity to compute homotopy paths in a more efficient way. We demonstrate our method with the help of a numerical example.